2002
DOI: 10.3171/jns.2002.97.3.0692
|View full text |Cite
|
Sign up to set email alerts
|

Distal anterior inferior cerebellar artery aneurysms

Abstract: Aneurysms of the distal anterior inferior cerebellar artery (AICA) are rare; fewer than 100 cases have been reported. The authors detail their experience with four cases and present endovascular as well as microsurgical management options. The medical records and neuroimaging studies obtained in four patients who were treated at a single institution were reviewed. Clinical presentations, neuroimaging and intraoperative findings, and clinical outcomes were analyzed. There were three men and one woman; their mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 32 publications
1
78
0
Order By: Relevance
“…Incidences of peripheral AICA aneurysms on dorsolateral and caudomedial branches of the same vessel have been reported. 4 Zager and colleagues 63 have described a patient with a ruptured meatal loop aneurysm in whom 3 prior negative DS angiograms had shown no positive findings. Iwanga and associates 27 have described a peripheral aneurysm that was diagnosed on CT angiography but was previously undetected on 2 DS angiograms; the aneurysm eventually bled.…”
Section: Discussionmentioning
confidence: 99%
“…Incidences of peripheral AICA aneurysms on dorsolateral and caudomedial branches of the same vessel have been reported. 4 Zager and colleagues 63 have described a patient with a ruptured meatal loop aneurysm in whom 3 prior negative DS angiograms had shown no positive findings. Iwanga and associates 27 have described a peripheral aneurysm that was diagnosed on CT angiography but was previously undetected on 2 DS angiograms; the aneurysm eventually bled.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-meatal AICA aneurysms are extremely rare, with only 16 previous cases. [2][3][4][5][7][8][9][10]12,16,17,[19][20][21] Ten of these 16 patients were treated by microsurgical neck clipping 4,[8][9][10]17,[19][20][21] by opening the meatus with extensive nerve dissection, 5 patients underwent meatal loop trapping without bypass, 2,3,7,12,16) and one patient with unruptured aneurysm was managed by microsurgical packing of the internal auditory canal. 5) None of the 5 patients treated by simple meatal loop trapping developed cerebellar infarction, probably due to the favorable collateral blood supplies from dominant PICA and superior cerebellar artery.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][7][8][9][10]12,16,17,[19][20][21] Female prevalence (female/male=15/1) is remarkable, with mean patient age of 53 years. Most patients (15/16) developed subarachnoid hemorrhage (SAH) at the onset, [2][3][4][7][8][9][10]12,16,17,[19][20][21] and only one presented with hearing disturbance due to the mass effect of the aneurysm. 5) The pathological nature of intra-meatal aneurysm is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been reported only 17 AICA aneurysms treated by EVT, all of which were in the distal AICA and were treated by parent artery occlusion, except in 2 cases. [22][23][24][25]29,30,[40][41][42][43][44][45][46][47] The reasons for EVT in proximal AICA aneurysms may be as follows: 1) development of technologies regarding endovascular devices, 2) all treated aneurysms not fusiform but saccular, and 3) accessibility to anatomic configuration by an endovascular device. Because all the treated AICA aneurysms were saccular, it was possible to preserve the parent artery with endosaccular embolization, and stent-assisted coiling was also applied in cases of the wideneck AICA aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…The former can be treated by clip ligation at the neck, and the latter may be trapped or occluded surgically or endovascularly. 6,21,24,25,[29][30][31] The etiology of the AICA aneurysm is controversial: hemodynamic stress, embryonic vulnerability, flow-related vascular pathology, and arterial dissection by local trauma or nonspecific inflammation. 29,[32][33][34][35][36][37][38][39] Our study showed that 2 aneurysms were accompanied by AVMs and Moyamoya disease.…”
Section: Discussionmentioning
confidence: 99%